The 16th Venice Architecture Biennale celebrates the triumph of the ancient régime, but la lutte continue. Issue 1 (1st July 2019) - Somma, Paola
AbstractIn 1968 many intellectuals took to Piazza San Marco to express solidarity with the students of the Venice Academy of Fine Arts who were demonstrating against the Biennale and had been attacked for four hours by the police. In 2018 the same square was patrolled by armed troops deployed to 'protect the tourists' who occupied the city and there was no sign of protests against the Biennale. On the day of inauguration, the only voice of dissent was that of some citizens claiming their right 'to live here'. No trace of intellectuals. Many of the old protesters have made a comfortable career while the invited artists to the international exhibition have uncritically responded to the call of this year's Architecture Biennale, whose title is 'FREESPACE', without questioning the prevailing paradigm in which 'free' means 'space cleared from citizens and offered as a gift to financial investors'. Only a few national pavilions have adopted a more articulate attitude that might recall some of the May '68 aspirations. Retracing the events that transformed a public cultural institution into an enterprise at the service of the art market and a powerful agent of the gentrification and Disneyfication of Venice over the last 50 years, this article focuses on the role played by the Architecture Biennale in the process. It also highlights the few contributions that in 2018 challenged the dominant narrative by explicitly referring to the notion and practice of conflict.